Empowering Growth: Driving the Implementation of Senegal's Climate-Smart Agriculture Investment Plan (CSAIP) - Ouedraogo, Issa; Girvetz, Evan Hartunian; Siagbe, Golli; Diouf, Latyr (2025)
The brief outlines the early implementation of Senegal’s Climate-Smart Agriculture Investment Plan (CSAIP), a national framework translating climate commitments into targeted agricultural investments. Developed under the Ministry of Agriculture with support from the Alliance of Bioversity International and CIAT through AICCRA and the World Bank, the CSAIP operationalizes climate ambition via geospatially guided interventions, blended finance mechanisms, and inclusive governance. Early outcomes show improved institutional coordination, increased bankable CSA opportunities, and expanded farmer access to digital climate services and finance tools. Through partnerships with projects like AVENIR, the CSAIP integrates soil health, water-smart irrigation, and digital decision-support tools to strengthen resilience and investment readiness. The framework positions Senegal as a continental leader in climate finance readiness and climate-smart agricultural transformation.